因为3a+4b=-2,2a-3b=1,且-6a²+ab+12b²=-(6a²-ab-12b²)=-(3a+4b)(2a-3b).所以所求代数式的值等于-(-2)(1)=2.
若3a+4b=-2,2a-3b=1,则-6a^2+ab+12b^2=
1个回答
相关问题
-
a^2+b^2=1,ab=12/25,则a+b=?,a^3+b^3=?,a^4-b^4=?,a^6-b^6=?
-
若a/(a-b)=1/2,则(3a²-5ab+2b²)/(2a²+3ab-6b²
-
若a+b=3,则2a^2+4ab+2b^2-6的值为 A.12 B.6 C.3 D.0
-
3(a3−a2b+12ab2)−12(6a3+4a2b+3ab2).
-
若a+b=3,ab=-2,则(4a-5b-3ab)-(3a-6b+ab)=______.
-
若a2+ab=3 b2+ab=6 则a+b=?
-
若正数a.b满足a^2/(a^4+a^2+1)=1/24,b^3/(b^6+b^3+1)=1/19,则ab/(a^2+a
-
若a、b满足a^2-3ab+2b^2=6,且a-2b=3,则a-b=?
-
若a-b=4,ab=1,求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)
-
若a-b=0则a^2*b^2分之a^4+3a^3b-2a^2b^2-4ab^3+b^4